LEGAL AGREEMENT AD/ART “PT. PERKEBUNAN NUSANTARA IX” AFTER THE CONSOLIDATED PTP XV-XVI (PERSERO) WITH PTP XVIII (LIMITED) - Achmad Jumeri Pamungkas; Meilyna Dwijanti (UNISSULA, 2018)
Articles of Association of the Limited Liability Company is a legal basis that is used as reference in the management of the Company. The company can carry out cooperation with other parties. One such partnership is the amalgamation or consolidation of one or two companies into a single management company. in accordance with the process and the provisions of the legislation in force. In the Agreement clearly contain 1) the name and domicile of the Company; 2) the purpose and objectives and business activities of the Company; 3) The period of the founding of the Company; 4) the amount of the authorized, issued and paid-up capital; 5) the number of shares, class of shares if there is the following number of shares for each classification, the rights attached to each share, and the nominal value of each share; 6) the name of position and the number of members of the Board of Directors and Board of Commissioners; 7) determination of the place and manner of implementation of the GMS; 8) procedures for the appointment, replacement, dismissal of members of the Board of Directors and Board of Commissioners; 9) procedures for the use of profits and dividend distribution.